STRATEGI SEGMENTASI PASARAN PRODUK DALAM PERANCANGAN DAKWAH - Maryam Binti Abd. Majid (Islam Realitas: Journal of Islamic and Social Studies, 2017)
Da’wah is a mandatory requirement to be implemented by all Muslims. Da’wah planning and execution require a rigorous strategy to ensure the success of the Da’wah undertaken. This paper highlights one of the marketing strategies of the relevant product seen to be applied in the planning of the Da’wah of market segmentation. This study is an analysis of the text through documentation method. Market segmentation strategy involved in the design of propaganda using the basic outlines for each segment of the target, determine the profile, characteristics attraction towards the target, determines the number of segments, determine the location and form of the marketing mix for a given target segment propaganda Dakwah merupakan suatu tuntutan wajib untuk dilaksanakan oleh semua umat Islam. Pelaksanaan dakwah memerlukan perancangan serta strategi yang rapi bagi memastikan kejayaan proses dakwah yang dilaksanakan. Kajian ini mengutarakan salah satu strategi pemasaran produk yang dilihat relevan untuk diaplikasi dalam perancangan dakwah yaitu segmentasi pasaran. Kajian ini adalah analisis teks menerusi metode dokumentasi. Strategi segmentasi pasaran diaplikasi dalam perancangan dakwah menerusi kaedah menggariskan asas bagi setiap segmen sasaran, menentukan profil, ciri-ciri tarikan terhadap sasaran, menentukan jumlah segmen, menentukan lokasi serta membentuk campuran pemasaran bagi segmen sasaran dakwah yang ditentukan.